2023
DOI: 10.1200/jco.21.02698
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes and Roles of Transplantation and Maintenance Rituximab in Patients With Previously Untreated Mantle Cell Lymphoma: Results From Large Real-World Cohorts

Abstract: PURPOSE Commonly used first-line (1L) treatments for mantle cell lymphoma include high-dose cytarabine-based induction followed by autologous stem-cell transplant (ASCT) for younger patients and several chemoimmunotherapy regimens for older patients. Continuous debates exist on the role of ASCT in younger patients and maintenance rituximab (MR) after bendamustine plus rituximab (BR). METHODS Retrospective data from 4,216 patients with mantle cell lymphoma in the Flatiron Health electronic record-derived deiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 34 publications
1
49
1
Order By: Relevance
“…12 Interestingly, the Flatiron health electronic study retrospective analysis suggested that BR 1 R-maintenance without ASCT may provide similar outcome. 13 In future trials, ASCT may be challenged if cytarabine induction or BR complemented by targeted approaches such as BTK-inhibitors 14 achieves similar long-term results to prevent long-term toxicities. Accordingly, the TRIANGLE (ClinicalTrials.gov identifier: NCT02858258) and E4151 protocols (ClinicalTrials.gov identifier: NCT03267433) are investigating the role of ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…12 Interestingly, the Flatiron health electronic study retrospective analysis suggested that BR 1 R-maintenance without ASCT may provide similar outcome. 13 In future trials, ASCT may be challenged if cytarabine induction or BR complemented by targeted approaches such as BTK-inhibitors 14 achieves similar long-term results to prevent long-term toxicities. Accordingly, the TRIANGLE (ClinicalTrials.gov identifier: NCT02858258) and E4151 protocols (ClinicalTrials.gov identifier: NCT03267433) are investigating the role of ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…In one recent analysis, 49% of patients older than 65 years received BR during 2010-2015. 35 However, there remains wide variability in practice among both community oncologists and lymphoma specialists.…”
Section: Recent Trends In Induction Therapymentioning
confidence: 99%
“…The relevant literature regarding frontline therapy is then reviewed, with particular focus on selection of induction regimen and the potential roles for autologous transplantation and/or rituximab maintenance. This literature primarily consists of prospective phase 2 and phase 3 clinical trials; however, added to this literature now is a growing body of large retrospective real-world cohorts, such as the new analysis by Martin et al, 35 the manuscript that accompanies this Oncology Grand Rounds article. In some cases, the real-world evidence is at odds with data from prospective clinical trials, such as regarding the role of rituximab maintenance after bendamustine plus rituximab induction.…”
mentioning
confidence: 99%
“…We used similar criteria to define lines of therapy as those applied in the Flatiron Health dataset. 10 For example, any nonrituximab chemoimmunotherapy agent given within a 30-day window or rituximab within 90-day window was considered as the same line.…”
Section: To the Editormentioning
confidence: 99%
“…10,13,14 However, due to the inconsistency of findings and some limitations of these studies, there remains uncertainty in the clinical benefit. Two prior observational studies 10,13 showed similar benefits in the multivariable analysis. In contrast, the MAINTAIN trial showed no significant difference in PFS or OS between the RM and non-RM groups, despite the longer median PFS observed with RM (not reached vs. 55 months for non-RM).…”
Section: To the Editormentioning
confidence: 99%